A Sociological Analysis of the Destructive Motivation of Public Servants: Causes and Avoidance - Vasilieva, Alena Aleksandrovna; Borisov, Alexander Fedoseevich; Narozhnaia, Diana Anatolievna; Kyrtyak, Ivan Vladimirovich; Vorontsov, Yaroslav Alekseevich (International Journal of Criminology and Sociology, 2021)
The article deals with a study of the destructive motivation of public servants on the example of the Republic of Sakha (Yakutia). The study was conducted from 2015 to 2018. The purpose of study was to determine what factors are demotivating for civil servants. The research method was the questionnaire method based on a stratified quota sample. It has been proven that this type of motivation in governmental bodies is primarily caused by the employees’ disappointment in expectations. Public service is attractive mainly due to the stability of employment and the high social status of an official. However, public servants have to deal with a lack of real power, a high level of stress, and work intensity. Also, the respondents consider their income as inadequate to their work and social status. As a result, employees tend to minimize their labor costs, and destructive motivation appears. The practice of personnel management applies several measures to eliminate this phenomenon, but not all of them can be implemented for the public service. The authors regard the following means as the most effective ones, namely: the improvement of labor organization, the automatization of routine operations, personal responsibility increase, and the development of decision-making discretion.